Pengaruh Model Pembelajaran Discovery Learning Berbantuan Media Lectora Inspire Dalam Meningkatkan Motivasi dan Hasil Belajar Fisika - Liyani, Meril; Zohri, Muhammad; Bahtiar (Alpatih Harapan Semesta, 2023)
This study aims to determine whether there is an effect of discovery learning model assisted by lectora inspire media in improving motivation and learning outcomes in Physics at MAN 1 West Sumbawa. The type of research used in this research is quasi experiment. The population in this study as well as the research sample was 38 students. Previously, learning used a conventional model, in this case the researcher applied a new innovation by applying the discovery learning model. Data collection techniques are tests, questionnaires and documentation. Based on the results of the analysis of the final test (posttest) experimental class average value of 82.37 and control class 66.32. Based on the results of data analysis using the t-test, the t-count is 8.468 and the t-table at the significance level of 0.005 is 2.878, then the t-count> t-table. The results of the analysis of learning motivation of the experimental class obtained an average value of 59.05 and the control class 52.68. Based on the results of data analysis using t-test obtained t-count of 7.596 and t-table at a significance level of 0.005 of 2.878, then t-count> t-table. It can be concluded that there is an effect of discovery learning model assisted by lectora inspire media in increasing motivation and learning outcomes in Physics at MAN 1 West Sumbawa.